Winterkill - Skrypuch, Marsha Forchuk (Scholastic Inc., 2022)
Despite their political differences Nyl, a young Ukrainian farmer, and Alice, a Canadian girl whose father has come to the Soviet Union, struggle to survive the famine-genocide known as the Holodomor, when the forced collectivization of the Ukrainian farms and hard winters led to mass starvation and death.